543miR-19a replacement rescues cardiac and fin defects in zebrafish model of holt-oram syndrome. (15th July 2014) - Chiavacci, E; Cremisi, F; Guzzolino, E; Cellerino, A; Baumgart, M; D'aurizio, R; Pitto, L
Abstract: Purpose: MicroRNAs (miRNAs) are short, single-stranded RNAs that anneal with complementary sequences in mRNAs thereby suppressing protein expression and often decreasing mRNA stability. Due to the high number of genes that are potentially targeted by one miRNA and to the relatively low number of different miRNAs coded in the genome, miRNAs are the best candidates to orchestrate gene expression in embryonic development and in response to inducing signals, by integrating distinct transcription factors pathways. Indeed, the manipulation of miRNA expression or function can have a profound impact on cellular phenotype. miRNA are critically involved in almost all the biological processes in health and disease including several cardiovascular disorders. Tbx5 is a transcription factor crucial for heart development and implicated in cardiac function. In human, TBX5 mutations are associated with Holt-Oram Syndrome (HOS), which is characterized by upper limb and congenital heart defects. In mouse model of HOS, expression profiling revealed that Tbx5 regulates hundreds of genes through complex transcriptional networks, acting both directly on gene expression and indirectly as "regulating of regulators". Our data indicate that miRNAs can be important effectors of Tbx5. The goal of our project is to better characterize the miRNAs/Tbx5 regulatory network with the aim: a) to understand the molecular roots of the complex HOS phenotype; b) to verify if it might be possible, by miRNA modulation, to restore the aberrant pathways generated by Tbx5 alteration. Methods: Using zebrafish as model systems of HOS, we characterized the miRNA profiles of wild type (WT) and Tbx5-depleted embryos by NGS. The impact of differentially expressed miRNAs on cardiac development of WT embryos and Tbx5 morphants was investigated by gain and loss of function experiments. Results: Among the identified miRNAs responsive to Tbx5 dosage we focused on miR-19a, whose expression decreases in HOS zebrafish embryos. We showed that: a) miR-19a dysregulation affects heart development; b) miR-19a modulates the expression of genes important for epicardial development and retinoic acid metabolism; c) miR-19a replacement was able to rescue cardiac and pectoral fin defects and increase the viability of Tbx5 morphants. Conclusions-Our data demonstrate that in zebrafish the modulation of a single miRNA is sufficient to reduce the defects generated by a complex syndrome like HOS, supporting enthusiasm for the continued exploration of miRNAs as a new class of drug target.